Synthesis of trans N-Substituted Pyrrolidine Derivatives Bearing 1,2,4- triazole Ring - Prasad, Tangella N.; Reddy, Yeruva Pavankumar; Settipalli, Poorna Chandrasekhar; Kumar, Vadiga Shanthi; Reddy, Eeda Koti; Basha, Shaik Firoj; Anwar, Shaik (Current Organic Synthesis, 2022)
Background: 1,2,4-triazoles scaffolds display significant biological activities due to hydrogen bonding, solubility, dipole character, and rigidity. Objective: The core motif of 1,2,4-triazoles plays a vital role in clinical drugs such as Rizatriptan (antimigraine), Ribavirin (antiviral), anastrozole (anticancer), etizolam (anxiolytic), estazolam (anticonvulsant), alprazolam (anti-hypnotic), letrozole (aromatase inhibitor), loreclezole (anticonvulsant), trazadone (antidepressant) etc. Methods: Epoxide ring opening of tert-butyl 6-oxa-3-azabicyclo [3.1.0] hexane-3-carboxylate followed by methylation under basic conditions and de-protection gave the corresponding trans 1-(4- methoxypyrrolidin-3-yl)-1H-1,2,4-triazole hydrochloride salt as the precursor. This precursor on reaction with substituted benzoyl chlorides and benzyl bromides gave the desired amide and amine products. Results: A library of 14 N-substituted pyrrolidine derivatives i.e. trans3-methoxy-4-(1H-1,2,4-triazol- 1-yl) pyrrolidin-1-yl) (phenyl)methanone and trans 1-benzyl-4-methoxypyrrolidin-3-yl)-1H-1,2,4- triazole were prepared. Conclusion: Eight novel amides (6a-h) and six amines (8a-f) derivatives were synthesized using 1-(4- methoxypyrrolidin-3-yl)-1H-1,2,4-triazole 4 salt with substituted benzoyl chlorides and benzyl bromides.
Keywords: 4- triazole